Purification and characterization of a recombinant beta-glucosidase in Escherichia coli - Thi Binh, Nguyen; Thi Quy, Nguyen; Thu Hong, Le Thi; Nam Hai, Truong (Vietnam Journal of Biotechnology, 2022)
Beta-glucosidase (BGL) is an enzyme involved in the degradation of cellulose and plays an essential part in many biological processes. Currently, most BGLs applied in the industry are derived from fungi. Exploring novel BGLs with desired properties is attractive. The recombinant BGL derived from microorganisms surrounding white-rot fungus in Cuc Phuong National Park was successfully expressed in Escherichia coli Rosetta 1 (denoted as the GH3S2 gene). The protein GH3S2 was purified by an affinity chromatography column using buffer PBS 50 mM (NaCl-free) pH 7, and the enzyme was collected in buffer containing imidazole 300 mM. The purity and content of the purified protein was determined. The purity of the enzyme obtained after purification reached over 95%. The result of the GH3S2 protein content in the purified sample was 1.54 mg/ml. Thus, amount of the purified GH3S2 obtained from one liter of bacterial culture was 41.80 mg. The final GH3S2 was purified approximately 7.05–fold with a purification yield of 40.06%. The purified enzyme was used to study the properties. This enzyme optimally was activated at 37oC and pH 6.0. At this condition, the enzyme specific activity was 2.23 U/mg in the pNPG substrate, and Km and Vmax were, respectively, 4.55 mM and 4.91 μmol/min. Its activity increased to 200% and 119% in the presence of Ca2+ and Mg2+ and decreased to 33% and 14% when Ni2+ and Cu2+ were added. The enzyme activity was maintained at 70% when the glucose concentration was at 6 mM and then gradually decreased.